The Dynamic Relationship between Real Interest Rate and Investment: An Empirical Analysis for Selected Pacific Island Countries - Bano, Shabnam Sazma (International Journal of Economics and Financial Issues, 2018)
This study investigates the short run and long run relationship between real interest rate and investment for selected PICs using a PMG - Panel ARDL approach for the period 1980 to 2016. The study reveals a significant negative relationship between real interest rate and investment in long run while a positive relationship in short run across all PICs, except for Samoa. The PMG results further show that economic variables such as growth rate, communication, foreign investment, aid and real exchange rate are investment creating in the long run while savings rate is investment reducing. In the short run only foreign direct investment and economic growth is investment creating while all other variables are investment reducing. The speed of adjustment is also a good predictor and reflected that stability will be restored across all countries in the long run. The achieved results have important policy implication for the PICs. Keywords: Panel ARDL, investment, real interest rate, PICs JEL Classifications: E01, E22, E43, E61 https://doi.org/10.32479/ijefi.6827